Probing the Location and Speciation of Elements in Zeolites with Correlated Atom Probe Tomography and Scanning Transmission X‐Ray Microscopy. Issue 1 (31st October 2018) - Schmidt, Joel E.; Ye, Xinwei; van Ravenhorst, Ilse K.; Oord, Ramon; Shapiro, David A.; Yu, Young‐Sang; Bare, Simon R.; Meirer, Florian; Poplawsky, Jonathan D.; Weckhuysen, Bert M.
Abstract: Characterizing materials at nanoscale resolution to provide new insights into structure property performance relationships continues to be a challenging research target due to the inherently low signal from small sample volumes, and is even more difficult for nonconductive materials, such as zeolites. Herein, we present the characterization of a single Cu‐exchanged zeolite crystal, namely Cu‐SSZ‐13, used for NOX reduction in automotive emissions, that was subject to a simulated 135, 000‐mile aging. By correlating Atom Probe Tomography (APT), a single atom microscopy method, and Scanning Transmission X‐ray Microscopy (STXM), which produces high spatial resolution X‐ray Absorption Near Edge Spectroscopy (XANES) maps, we show that a spatially non‐uniform proportion of the Al was removed from the zeolite framework. The techniques reveal that this degradation is heterogeneous at length scales from micrometers to tens of nanometers, providing complementary insight into the long‐term deactivation of this catalyst system. Abstract : Look closely : Probe Tomography (APT) and Scanning Transmission X‐Ray Microscopy (STXM) have been used to study the same single crystal of Cu‐exchanged zeolite SSZ‐13, an automotive emissions reduction catalyst, to gain a better picture of how the catalyst ages using two high spatial resolution techniques.